When a Friend Becomes Your Enemy: Natural Killer Cells in Atherosclerosis and Atherosclerosis-Associated Risk Factors - Palano, Maria Teresa; Cucchiara, Martina; Gallazzi, Matteo; Riccio, Federica; Mortara, Lorenzo; Gensini, Gian Franco; Spinetti, Gaia; Ambrosio, Giuseppe; Bruno, Antonino (Frontiers in Immunology, 2022)
Cardiovascular diseases (CVDs) represent the first cause of death worldwide. Atherosclerosis, the change in structure and function of arteries with associated lesion formation and altered blood flow is the leading cause of CVDs. Beyond dyslipidemia, chronic inflammation, together with aberrant phenotype and function of cells of both the innate and adaptive immune system are now recognized as relevant contributors to atherosclerosis onset and progression. However, while the role of macrophages and T cells in atherosclerosis has been addressed in several studies, Natural Killer (NK) cells represent a poorly explored immune cell type that deserves attention due to NK cell emerging contribution to vascular homeostasis. Furthermore, the possibility to re-purpose the immune system has emerged as a relevant tool to design new therapies, with success in the field of cancer immunotherapy. Thus, a deeper knowledge of NK cell pathophysiology in the context of atherosclerosis could help developing new preventive and treatment strategies. Here, we review the current knowledge about NK cell phenotype and activities in atherosclerosis and selected atherosclerosis risk factors, type-2 diabetes and obesity, and discussing the related NK-cell oriented environmental signals.